2001
DOI: 10.1128/cdli.8.6.1060-1063.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles of Pediatric Patients Treated with Antibiotics for Pyelonephritis: Potential Therapeutic Impact

Abstract: Urinary tract infections are common in infants and children. Pyelonephritis may result in serious complications, such as renal scarring, hypertension, and renal failure. Identification of the timing of release of inflammatory cytokines in relation to pyelonephritis and its treatment is essential for designing interventions that would minimize tissue damage. To this end, we measured urinary cytokine concentrations of interleukin-1␤ (IL-1␤), IL-6, and IL-8 in infants and children with pyelonephritis and in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
37
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 38 publications
9
37
1
3
Order By: Relevance
“…Except for higher levels of TNF-a and IL-12, and lower levels of IL-18 in the ASB group as compared with negative controls, we found no differences between the groups with regard to the pro-inflammatory cytokines IL-1b, TNF-a, IL-12, and IL-18, and this is in accordance with the findings of others [13,22,23].…”
Section: Discussionsupporting
confidence: 93%
“…Except for higher levels of TNF-a and IL-12, and lower levels of IL-18 in the ASB group as compared with negative controls, we found no differences between the groups with regard to the pro-inflammatory cytokines IL-1b, TNF-a, IL-12, and IL-18, and this is in accordance with the findings of others [13,22,23].…”
Section: Discussionsupporting
confidence: 93%
“…IL-6 promotes the growth and differentiation of T and B lymphocytes. Kassir et al reported that elevated IL-6 confirmed the inflammatory process, and that IL-6 levels rapidly decreased after appropriate antibiotic treatment [6]. The findings in the current study are not consistent with this observation.…”
Section: Discussioncontrasting
confidence: 99%
“…Some authors have attempted to identify markers of inflammation in urine and to use them in the diagnosis of infection of the urinary tract and in monitoring response to therapy [3][4][5][6].…”
mentioning
confidence: 99%
“…They are involved in B cell and T cell proliferation and neutrophil chemoattraction, along with secretion of CRP, immunoglobulins, and acute-phase proteins (2,6,8,10) Clinical manifestations of APN depend on the production of different cytokines, and measurement of urinary ILs seems to be useful for the rapid diagnosis and localization of inflammation within the urinary tract system. Increased urinary IL-1, IL-4, IL-6, and IL-8 concentrations have been reported in children with acute febrile UTIs compared to the healthy children and those with lower UTIs, asymptomatic bacteriuria, and non-renal febrile infections (2,(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the determination of urinary ILs is helpful for the evaluation of treatment response in APN, and persistently elevated urinary IL concentrations indicate treatment modifications (6,9,17). Accordingly, increased urinary IL levels decreased following antibiotic treatment and were considered for therapeutic monitoring in our patients.…”
Section: Discussionmentioning
confidence: 99%